Using the “Brainstorming” method in the analysis of simple sentences - Kamilova Tursunoy Rustamjon qizi (Periodica Journal, 2023)
The method of "mental attack" - a method that collects free ideas and feedback from students on a problem, through which a certain solution is reached. There are written and oral forms of the method of "mental attack". Each student expresses his / her opinion orally to the question asked by the educator in oral form. Learners state their answers clearly and concisely. In writing, learners write their answers to the question on paper cards in a short and visible way. The answers are fastened to the board (using magnets) or to a “pinboard” board (using needles). In the written form of the "mental attack" method, it is possible to group the answers according to certain characteristics.
Keywords: attack; syntax; simple speech; phrase